العلاقات الدلالية ودورها في انسجام الحديث النبوي الشريف - بوترعة , عبد الحميد; زلومه, رقية; غوار, حكيمة (University of Eloued جامعة الوادي, 2024)
يهدف البحث إلى تحليل العلاقات الدلالية في أحاديث الأربعين النووية، مركزا على وضوح وثراء الحديث في هذه الأحاديث المختارة، يتناول البحث مسألة أنواع العلاقات الدلالية الموجودة في هذه الأحاديث ودورها في بناء المعنى وترابط الأفكار، ويحاول استخدام دراسات سابقة في هذا المجال لتوجيه التحليل والتفسير، تبدأ المذكرة بتقديم تاريخ البحث اللغوي، حيث يتمّ التأكيد على تحول الاهتمام من تحليل الجملة إلى تحليل النَّصوص كوحدة أساسية تحمل المعنى، يشير البحث إلى أهمية دراسة العلاقات الدلالية في تماسك النّصوص وارتباطها، وكيفية تأثير ذلك على فهم الحديث النبوي الشريف. يتم توجيه البحث نحو فصلين رئيسيْن، حيث يناقش الفصل الأول مفاهيم نصّية تشمل النّص، ونحو النّص والمعايير النّصية، مما يساعد في فهم السياق اللّغوي للحديث، بينما يتناول الفصل الثاني العلاقات الدلالية وتحليل دورها في تماسك الحديث النبوي، مستعرضا مختلف أنواع العلاقات كالإجمال والتفصيل والعموم والخصوص وغيرها. تعد المذكرة مساهمة مهمة في فهم الحديث النبوي وتحليله، وتقديم إطار لدراسة العلاقات الدلالية في النّصوص الدينية سة. The research aims to analyze the semantic relationships in the forty hadiths of al-Nawawi, focusing on the clarity and richness of the hadith in these selected hadiths. The research addresses the issue of the types of semantic relationships found in these hadiths and their role in constructing meaning and interconnecting ideas. It attempts to use previous studies in this field to guide analysis and interpretation. It begins with The memorandum presents the history of linguistic research, where emphasis is placed on the shift of interest from analyzing the sentence to analyzing texts as a basic unit that carries meaning. The research indicates the importance of studying the semantic relationships in the cohesion and connection of texts, and how this affects the understanding of the noble Prophet’s hadith. The research is directed towards two main chapters, where the first chapter discusses textual concepts that include the text, the grammar of the text and textual standards, which helps in understanding the linguistic context of the hadith, while the second chapter deals with the semantic relationships and analyzing their role in the coherence of the Prophet’s hadith, reviewing various types of relationships such as generality, detail, generality and specificity. And others. The memorandum is an important contribution to understanding and analyzing the Prophet’s hadith, and providing a framework for studying semantic relationships in religious texts.
دراسة نصية في أحاديث"الأربعون نووية
لسانيات عامة
Keywords: العلاقات الدلالية، أحاديث الأربعين النووية، الحديث النبوي; semantic relationships; hadiths of the forty nuclear hadiths; hadith of the Prophet.